Blood Leukocyte Counts and Genetic Polymorphisms of Alcohol Dehydrogenase‐1B and Aldehyde Dehydrogenase‐2 in Japanese Alcoholic Men. (25th February 2016) - Yokoyama, Akira; Brooks, Philip J.; Yokoyama, Tetsuji; Mizukami, Takeshi; Matsui, Toshifumi; Kimura, Mitsuru; Matsushita, Sachio; Higuchi, Susumu; Maruyama, Katsuya
Abstract : Background: Roughly 40% of East Asians have inactive aldehyde dehydrogenase‐2 (ALDH2) encoded by the ALDH2*2 allele, and 90% have highly active alcohol dehydrogenase‐1B (ADH1B) encoded by the ADH1B*2 allele. Macrocytosis and macrocytic anemia in alcoholics have been associated with ADH1B and ALDH2 gene variants which increase acetaldehyde (AcH) levels. Methods: We investigated the relationship between ADH1B*2, ALDH2*2, and leukocyte counts of Japanese alcoholic men ( N  = 1, 661). Results: After adjusting for age, drinking habits, smoking habits, body mass index, presence of liver cirrhosis, and serum levels of C‐reactive protein, we found that total and differential leukocyte counts were lower in the presence of the ALDH2*1/*2 genotype (vs. ALDH2*1/*1 genotype). ALDH2*2/*2 carriers were not found in our study population. Leukocyte, granulocyte, and monocyte counts were also lower in the presence of ADH1B*2 (vs. ADH1B*1/*1 genotype), but the lymphocyte count was higher. The ALDH2*1/*2 genotype was associated with leukocytopenia (<4, 000/ μ l; adjusted odds ratio [95% confidence interval] = 1.89 [1.27 to 2.80]), granulocytopenia (<2, 000/ μ l; 1.86 [1.22 to 2.82]), monocytopenia (<250/ μ l; 2.22 [1.49 to 3.29]), and lymphocytopenia (<1, 000/ μ l; 1.93 [1.32 to 2.83]). In contrast, the ADH1B*2 had the opposite effect on lymphocytopenia (0.65 [0.46 to 0.93]). Considering genotype effects under conditions of immune stimulation, we observed suppressive effects of ADH1B*2 allele on leukocytosis (≥9, 000/ μ l; 0.69 [0.50 to 0.97]), granulocytosis (≥6, 500/ μ l; 0.66 [0.47 to 0.93]), and monocytosis (≥750/ μ l; 0.56 [0.39 to 0.79]). The ADH1B*2 plus ALDH2*1/*2 combination had the greatest suppressive effects on the leukocyte, granulocyte, and monocyte counts. Conclusions: The total and differential blood leukocyte counts of Japanese alcoholics were strongly affected by their ADH1B and ALDH2 gene variants. High AcH exposure levels probably play a critical role in the suppression of blood leukocyte counts in alcoholics.